ESG Performance, Financial Ratios, Stock Prices, and Dividend Payments: Manufacturing and Energy Companies - Siti Nur Aisyah; Ana Yuliana Jasuni; Febri Wulandari Ansori; Agung Maulana (Eastasouth Institute, 2026)
Industrialization has led to an increase in environmental problems, resulting in higher demands for companies to adopt Environmental, Social, and Governance (ESG) principles. ESG practices involve a trade-off for companies between ESG performance, which requires large investments and has the potential to sacrifice shareholder profitability in the short term. This study aims to examine the influence of ESG performance, profitability ratios Return on Assets (ROA) and Return on Equity (ROE), and closing stock price on the Dividend Payout Ratio (DPR) for manufacturing and energy companies with high emissions in Indonesia from 2018 to 2023. The model used is panel data regression with a random effects approach. The results show that only ROE and the Governance (G) pillar have a significant positive effect on DPR, while the other variables are not significant. These findings indicate that dividend policy is still profit-based and that governance influences dividend policy considerations.